KONSISTENSI PELAKSANAAN SALAT TARAWIH BERJAMA’AH DI MASJID AL-JIHAD DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Hasan, Hasan (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
Ramadan is a special month, the Head of all months, a month that is more glorious than a thousand months and a month with a myriad of advantages, one of which is the implementation of tarawih prayers which are only found in the holy month of Ramahan. This study aims to determine the consistency of the implementation of the Tarawih prayer in congregation at the Al-Jihad Mosque, Kubang Jaya Village, Siak Hulu District, Kampar Regency, Riau Province 1446 AH/2025 AD. As well as to find out the reasons for people who are not consistent in carrying out Tarawih prayers in congregation at the Al-Jihad Mosque, Kubang Jaya Village, Siak Hulu District, Kampar Regency, Riau Province 1446 H./2025 AD. This research uses Qualitative research method and this research is population research. The subject of this research is the consistency of the implementation of Salat Tawarih in congregation at Masjid Al-Jihad. The results of this study are as follows: The congregation of Al-Jihad Mosque who consistently (always) perform Tarawih prayer in congregation in the holy month of Ramadan 1446 H./2025 M as many as 32 people (29, 09%).Category often as many as 9 people (8, 18%). Sometimes as many as 17 people (15, 45%) and the category never as many as 52 people (47, 27%).